1999
DOI: 10.1046/j.1440-1746.1999.01912.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of endoscopic ultrasonography as an indicator for surgical treatment of gastric cancer

Abstract: We applied these new criteria to 262 patients and found that the patients who had limited operation had the same prognosis and a better quality of life compared with patients who had the conventional operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
2
0
4
Order By: Relevance
“…Based on these previous studies, EMR was indicated to elevated intestinal type EGC of less than 2 cm and depressed diffuse type cancers of less than 1 cm [23]. Also, local gastrectomy without lymphadenectomy was indicated to mucosal cancers of less than 2 cm and to elevated submucosal cancers of less than 1 cm [4,24]. Recently, micro-LN metastasis has been investigated in various cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these previous studies, EMR was indicated to elevated intestinal type EGC of less than 2 cm and depressed diffuse type cancers of less than 1 cm [23]. Also, local gastrectomy without lymphadenectomy was indicated to mucosal cancers of less than 2 cm and to elevated submucosal cancers of less than 1 cm [4,24]. Recently, micro-LN metastasis has been investigated in various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…b For one patient with LN metastasis detected by postoperative HE staining, no CK-positive cells were found newly sliced sections of LNs. was indicated to mucosal cancers of less than 2 cm and to elevated submucosal cancers of less than 1 cm [4,24]. Recently, micro-LN metastasis has been investigated in various cancers.…”
Section: Location Of Metastatic Lnsmentioning
confidence: 99%
“…Başka bir çalışmada ise mide kanseri evrelemesinde EUS'un tanısal doğruluk oranı, bütün evreler ile T1, T2, T3 ve T4 evreleri için sırasıyla %77-88, %79-100, %63.3-73.9, %85.7-95 ve %72.7-100 rapor edilmiştir. Aynı çalışmada lenf nodu evrelemesi için tanısal doğruluk oranı %65-80, sensitivite: %66.7-%91; spesifite ise %73.7-84 bulunmuştur 34 . Multidedektör BT ile EUS'un çalışmalarda T evresini saptamada Lenf nodu evrelemesinde ise multidedektör BT ile EUS arasında fark görülmemiştir 35 .…”
Section: Gereç Ve Yöntemunclassified
“…Baflka bir çal›flmada ise mide kanseri evrelemesinde EUS'un tan›sal do¤ruluk oran›, bütün evreler ile T1, T2, T3 ve T4 evreleri için s›ras›yla %77-88, %79-100, %63.3-73.9, %85.7-95 ve %72.7-100 rapor edilmifltir. Ayn› çal›flmada lenf nodu evrelemesi için tan›sal do¤ruluk oran› %65-80, sensitivite: %66.7-%91; spesifite ise %73.7-84 bulunmufl (37). Mide kanserlerinde yap›lan EUS ile lokal evreleme ifllemi en az %30 vakada tedaviyi de¤ifltirmekte ve s›n›rl› rezeksiyonlar yap›lmakta-d›r (37).…”
Section: B M‹de Kanser‹ Evrelemes‹nde Eusunclassified
“…Ayn› çal›flmada lenf nodu evrelemesi için tan›sal do¤ruluk oran› %65-80, sensitivite: %66.7-%91; spesifite ise %73.7-84 bulunmufl (37). Mide kanserlerinde yap›lan EUS ile lokal evreleme ifllemi en az %30 vakada tedaviyi de¤ifltirmekte ve s›n›rl› rezeksiyonlar yap›lmakta-d›r (37). Mide kanserlerinde de TNM s›n›flamas› kullan›lmakla birlikte, 1997 sonras› lenf nodu evrelemesi de¤iflmifl, lenf Endoskopik ultrasonografi ile kanser evrelemesi nodlar›n›n lokalizasyonundan çok; lenf nodu say›s› üzerinde durulmufl ve NO, N1, N2, N3 fleklinde düzenlenmifltir.…”
Section: B M‹de Kanser‹ Evrelemes‹nde Eusunclassified